Magnetohydrodynamic micropolar nanofluid flow over a wedge with chemical reaction - Siti Norfatihah, Zulkifli; Norhafizah, Md Sarif; Mohd Zuki, Salleh; A., Samsudin (IOP Publishing, 2020)
In this paper, the flow of electrically conducting micropolar nanofluid flow over a wedge with the effect of chemical reaction is considered. A new boundary condition that assumed nanoparticle flux at the surface to be zero is incorporated in this study. This boundary condition is more physically acceptable due to the condition of nanoparticle volume fraction at the boundary that is passively controlled. In order to obtain the numerical solution, a set of similarity transformation variable was applied to reduce the governing non-linear partial differential equations to non-dimensional ordinary differential equations. The following non-linear ordinary differential equations are solved numerically using Runge-Kutta-Fehlberg (RKF45) method. Based on our findings, concentration profile is enhanced with uprising value of chemical reaction parameter.